Dynamic response analysis of a nose landing gear system of a propeller aircraft by finite element method - Suresh, K.; Vasanthanathan, A.; Nagaraj, P.; Karthik, N. Selva (Journal of Structural Engineering, 2024)
The main problem in the landing gear dynamics of the aircraft is either shimmy or brake induced vibration or groundinduced longitudinal and lateral excitation due to runway unevenness. Neither of these vibrations is catastrophic, butstill causes huge discomfort to pilots and passengers. Investigations on brake vibration were required, where a studyof landing gear vibration due to brake chatter and squeal during taxi and landing was performed. It is essential toanalyze vibration in aircraft due to the fact that while take-off and landing a very massive force acts on the landinggear, which tends to produce kinetic energy. Vibration would leads to the gradual deterioration of aircraft structure,which in turn affects both the passengers and crew. All vibrations have associated frequencies and magnitudes thatshould be identified. Basic dynamic theoretical studies of landing gear by modal and frequency response analysis usingfinite element method points out the design considerations required to reduce the level of vibration. An attempt hasbeen made to reduce the vibration by providing stiffeners at the sensitive locations obtained using strain energy valuesand results were presented and compared for nose landing gear with and without stiffeners.